Berenstain Bears (The) / : and Too much birthday - Berenstain, Stan (New York : Random House, 1986)
Sister Bear is distressed that thigns don't go quite at ther brithday party.
Keywords: Bears-Fiction; Birthdays-Fiction; Parties-Fiction